The Correlation Between Students' Vocabulary Mastery and Reading Comprehension: A Meta Analysis - Yusmawati Giawa; Nelson Balisar Panjaitan (Jurnal Bahasa Inggris Terapan, 2021)
Abstract The present Meta-Analysis was conducted to synthesize information across similar studies. This research employed a descriptive qualitative approach. The data of this study was 23 similar studies which focused on correlation between vocabulary mastery and reading comprehension that involved 1135 sample. The data contained r and n. r is a coefficient value and n are respondents. In collecting the data, the researchers used five steps, namely: Collecting studies or meta-analysis materials; Calculate the effect size of each study; Estimate the summary effect or mean effect size; Moderator variable analysis; Publication bias evaluation. The software that was utilized to analyses the data was JASP. Since K = 23, so 5K+10 = 125. The fail- safe N value obtained is 4727.000, with a significant target of 0.05 and p < 0.001. Because the safe value of N > 5K+10, it can be concluded that there is no publication bias problem in the Meta-Analysis study.